As empresas multinacionais e sua vinculação aos direitos humanos - Preiss, Celso Matheus (2025)
Human rights were traditionally conceived to shield subjects from the arbitrariness exercised by the Sovereign. Subsequently—already in the contemporary era—they were severely challenged by violations perpetrated by authoritarian governments, most notably by the National-Socialist regime. They are now once again being put to the test in a different challenge. Today, new social forces endowed with significant economic and influential power have emerged to challenge human-rights dogmatics. These actors, however, are neither the Sovereign nor the modern State, but private entities possessing substantial financial resources. It is therefore urgent to address the issue, for replacing the classical duty-bearers in the human-rights relationship calls for renewed reflection on the matter. The risk is particularly acute in the case of multinational corporations. Such enterprises are highly elusive: they do not put down roots in a single jurisdiction but instead incorporate, to varying degrees, in several countries according to the advantages offered by each—especially those with lower social and economic development.